Validation of the leukocyte labeling procedure with a new kit for the preparation of technetium-99m exametazime injection. Issue 4 (April 2016) - Martinez, Teresa; Gallego Peinado, Marta; Sanchez Catalicio, Jose; Perez Angel, Florentina; Contreras Gutiérrez, Jose
Abstract : The labeling of leukocytes with technetium-99m ( 99m Tc)-HMPAO is a frequent procedure in our laboratory, which was first validated before initiation of clinical studies with the commercial kit of 99m Tc-D, L-hexamethylpropylene amine oxime ( 99m Tc-D, L-HMPAO), available from 1988. Recently, a new kit of exametazime has been introduced, with a similar composition and clinical indications, but with some technical improvements. Validation of the labeling procedure with this new kit is proposed, including a comparison between both commercial kits. Requirements for validation were achieved successfully and a comparative study showed no statistically significant differences; nevertheless, labeling of leukocytes may be expected routinely with the new kit on account of its longer shelf-life and lower cost.